Ibn Asyur, Maqashid Syariah dan Islah Alam: Dekonstruksi Syariah terhadap Lingkungan Hidup dalam Pembangunan Berkelanjutan - Samsul Hadi; Najma Taralia Farah; Fattah Setiawan Santoso (Universitas Cokroaminoto Yogyakarta, 2026)
Environmental degradation, such as flooding, deforestation, and global warming, represents a global crisis threatening human life. Islam as rahmatan lil 'ālamīn forbids natural exploitation and affirms the obligation to preserve environmental well-being through the Qur'an and Hadith. In classical doctrine, Imam al-Shāṭibī formulated maqāṣid al-sharī‘ah into five essential elements (al-kulliyyāt al-khams): the protection of religion, life, intellect, lineage, and wealth. However, the environmental dimension was not explicitly formulated. This study highlights the thought of Muhammad al-Ṭāhir Ibn ‘Āsyūr (19th century), who reconstructed maqāṣid al-sharī‘ah by incorporating ḥifẓ al-‘ālam (preservation of the environment) as a primary objective of Islamic law, grounded in textual evidence commanding ecological sustainability and prohibiting environmental destruction.